Demography and Nation : Social Legislation and Population Policy in Bulgaria - Baloutzova, Svetla (Book collections on Project MUSE., 2010)
Throughout centuries, authorities have put pains into 'engineering' their populations by attempting to regulate the birth and child mortality trends in either direction, or striving to achieve a desired 'population quality' design. The book contributes to the historical studies pursued in the social policy and population domain by channelling scholarly curiosity towards the less known path of East Europe. The monograph investigates the origins of state policy toward population and the family in Bulgaria. Reconstructs the evolution of state legislation in the field of social policy toward the family between the two World Wars, colored by concerns about the national good and demographic considerations. It sets the laws regarding family welfare in their framework of a distinctively cultural, historical and political discourse to follow the motives behind the legislative initiatives.